2019
DOI: 10.1186/s13073-019-0623-0
|View full text |Cite|
|
Sign up to set email alerts
|

De novo and inherited TCF20 pathogenic variants are associated with intellectual disability, dysmorphic features, hypotonia, and neurological impairments with similarities to Smith–Magenis syndrome

Abstract: Background Neurodevelopmental disorders are genetically and phenotypically heterogeneous encompassing developmental delay (DD), intellectual disability (ID), autism spectrum disorders (ASDs), structural brain abnormalities, and neurological manifestations with variants in a large number of genes (hundreds) associated. To date, a few de novo mutations potentially disrupting TCF20 function in patients with ID, ASD, and hypotonia have been reported. TCF20 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(56 citation statements)
references
References 52 publications
6
50
0
Order By: Relevance
“…We found in total four elements that are serious candidate for positive selection, falling in introns of Neurexin2 and TCF1-220 . Neurexin2 is involved in the neurotransmitter release [53], while TCF20-201 is a transcription factor associated with behavioral abnormalities [54, 55]. While this suggests a potential impact on the nervous system and behavior, and echoes our findings from a previous study on positive selection in green anoles [52], further investigations are needed to formally validate the causal role of these elements and discard the possibility that they are only linked to a causal variant under selection.…”
Section: Discussionmentioning
confidence: 53%
“…We found in total four elements that are serious candidate for positive selection, falling in introns of Neurexin2 and TCF1-220 . Neurexin2 is involved in the neurotransmitter release [53], while TCF20-201 is a transcription factor associated with behavioral abnormalities [54, 55]. While this suggests a potential impact on the nervous system and behavior, and echoes our findings from a previous study on positive selection in green anoles [52], further investigations are needed to formally validate the causal role of these elements and discard the possibility that they are only linked to a causal variant under selection.…”
Section: Discussionmentioning
confidence: 53%
“…PTBP3 is involved in cell growth and erythropoiesis [ 63 ]. Neurexins are involved in the neurotransmitter release [ 64 ], while TCF20-201 is a transcription factor associated with behavioral abnormalities [ 65 , 66 ]. While this suggests a potential impact on the nervous system and behavior, and echoes our findings from a previous study on positive selection in green anoles [ 62 ], further investigations are needed to formally validate the causal role of these elements and discard the possibility that they are only linked to a causal variant under selection.…”
Section: Discussionmentioning
confidence: 99%
“…Several of these studies have unraveled specific genes that are associated with rare Mendelian disorders, whereas others have identified numerous genes that contribute to similar disorders with shared phenotypes. In a recent study, Liu and colleagues analyzed exome sequencing and chromosomal microarray data and identified pathogenic mutations in TCF20 in 32 affected individuals from 31 unrelated families [5]. TCF20 encodes an SPRE-binding transcription factor that is strongly expressed in pre-migratory neural crest cells and is known to influence other transcription factors [6].…”
Section: Functional Relatedness Translating To Shared Phenotypesmentioning
confidence: 99%
“…Liu and colleagues found that commonalities in gene structure and function between TCF20 and RAI1 could explain the shared core clinical features and molecular effects [5]. In fact, TCF20 shares several essential protein domains with RAI1 , including N-terminal transactivation domains, zinc-finger-like plant homeodomains (PHD), and nuclear localization signal domains [6].…”
Section: Functional Relatedness Translating To Shared Phenotypesmentioning
confidence: 99%
See 1 more Smart Citation